Composite photocatalyst CaIn2S4 / T-COF, and preparation method and use thereof
Patent Information
- Application Number
- CN202611099837.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-23
- Publication Date
- 2026-10-16
AI Technical Summary
然而,从HMF到DFF的选择性氧化过程中,传统化学氧化方法易造成HMF的过度氧化与矿化分解,同时衍生出复杂的副产物
[0019] 1) In the constructed composite photocatalyst CaIn2S4/T-COF, amorphous plate-like CaIn2S4 is grown in situ on the surface of spherical T-COF, which can provide more reactive sites and shorten the transport path of photogenerated electrons, thereby significantly improving photocatalytic activity;
Smart Images

Figure CN122912922A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of photocatalysis technology, specifically relating to a composite photocatalyst CaIn2S4 / T-COF for photocatalytic hydrogen peroxide production coupled with 5-hydroxymethylfurfural oxidation, its preparation method, and its uses. Background Technology
[0002] Hydrogen peroxide (H2O2) is an environmentally friendly and highly efficient oxidant widely used in wastewater treatment, disinfection, and organic synthesis. Currently, the mainstream industrial method for large-scale hydrogen peroxide production is the anthraquinone oxidation process. However, this method is energy-intensive, complex, and prone to environmental pollution, failing to meet the requirements of green chemistry production. Utilizing solar energy as a driving force to directly synthesize H2O2 from water and oxygen through photocatalysis is considered a production method with great potential. In the photocatalytic H2O2 production process, pure oxygen and hole sacrificial agents (such as ethanol and isopropanol) are typically introduced to improve the efficiency. However, the use of pure oxygen and sacrificial agents not only increases the production cost of H2O2 but also results in the ineffective utilization of the oxidizing power of photogenerated holes, severely restricting the economic benefits and application prospects of the photocatalytic H2O2 production half-reaction.
[0003] 5-Hydroxymethylfurfural (HMF) is an important biomass platform compound that can be selectively oxidized to various value-added chemicals, including 2,5-dicarboxyfuran (DFF), 5-carboxyfuran-2-carboxylic acid (FFCA), and 2,5-furandicarboxylic acid (FDCA). Among these, DFF, as a multifunctional chemical, has significant applications in drug synthesis, functional polymer material preparation, and the development of antifungal agents. However, in the selective oxidation process from HMF to DFF, traditional chemical oxidation methods easily lead to over-oxidation and mineralization decomposition of HMF, while also generating complex byproducts. Therefore, there is an urgent need to develop green and efficient HMF oxidation catalytic systems. Photocatalytic oxidation is a mild, low-energy-consumption, controllable, and sustainable method. Choosing HMF as a substitute for the traditional hole sacrificial agent in a photocatalytic system can synergistically achieve the value-added conversion of H2O2 and HMF, which is of great research significance for optimizing process costs and realizing comprehensive resource utilization. Summary of the Invention
[0004] The purpose of this invention is to overcome the shortcomings of the existing technology and meet the needs of research and application in this field, and to provide a composite photocatalyst CaIn2S4 / T-COF with simple and easy preparation process, easy operation, high product stability and yield, maximized solar energy utilization efficiency, low production cost, and the ability to co-produce H2O2 and value-added chemical DFF, as well as its preparation method and uses.
[0005] To achieve the above objectives, the present invention first provides a composite photocatalyst CaIn2S4 / T-COF, which is a spherical core-shell structure formed by amorphous sheet-like CaIn2S4 covering the surface of T-COF.
[0006] This invention also provides a method for preparing the composite photocatalyst CaIn2S4 / T-COF, characterized by comprising the following steps:
[0007] 1) Using thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene as raw materials and acetonitrile as solvent,
[0008] Synthesizing spherical covalent organic framework material T-COF at room temperature;
[0009] 2) The composite photocatalyst CaIn2S4 / T-COF is obtained by combining the sheet-like CaIn2S4 with the T-COF through a hydrothermal reaction.
[0010] Preferably, step 1) involves adding thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene to acetonitrile, then adding acetic acid solution, ultrasonically stirring, and allowing the reaction to stand; centrifuging the reaction solution, washing the resulting solid, and drying it to obtain T-COF; step 2) involves ultrasonically dispersing the T-COF obtained in step 1) in pure water, adding CaCl2, InCl3·4H2O and thioacetamide, stirring, then pouring the reaction solution into a reaction vessel and heating it to react; after centrifugation, washing, and drying, the composite photocatalyst CaIn2S4 / T-COF is obtained.
[0011] More preferably, in step 1), the molar ratio of thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene is 1:1 to 2:1, the amount of acetonitrile used is 10 to 100 mL, and the amount of acetic acid solution is 6 to 12 mol / L. -1 The stirring is performed at room temperature for 1–30 min; the static reaction is allowed to stand at room temperature for 2–4 days; the washing is performed by washing with N,N-dimethylformamide, tetrahydrofuran, and ethanol 1–3 times each; the drying temperature is 60–100 °C, and the drying time is 24–48 hours.
[0012] In step 2), the amount of pure water used is 30-70 mL; the molar ratio of CaCl2, InCl3·4H2O and thioacetamide is 1:2:4 to 1:2:8; the stirring is carried out at room temperature for 10-60 min; the reaction vessel is a stainless steel high-pressure reaction vessel with a polytetrafluoroethylene liner; the heating reaction is carried out by heating the reaction vessel to 100-180℃ for 12-36 h; the washing is carried out by washing with water and ethanol 1-3 times each; the drying temperature is 60-100℃ and the drying time is 24-48 hours.
[0013] This invention further provides an application of the aforementioned composite photocatalyst CaIn2S4 / T-COF, wherein the application is in the application of light...
[0014] This technology enables the catalytic oxidation of HMF to DFF with high selectivity while simultaneously producing H2O2.
[0015] The preferred application method is as follows: a certain amount of the composite photocatalyst CaIn2S4 / T-COF and HMF are dissolved in pure water, the temperature is controlled at 20 ℃, and the mixture is stirred in the dark for half an hour in an air atmosphere. Then, the reaction is continuously irradiated for a certain period of time to obtain H2O2 and DFF; the ratio of HMF to pure water is 1 mg: 5 mL.
[0016] More preferably, the application method is as follows: the amount of the composite photocatalyst CaIn2S4 / T-COF is 1 to 4 times the mass of the HMF, the temperature is controlled by a cooling water circulation pump, and the photo-reaction time is 1 to 6 hours.
[0017] More preferably, the application method is as follows: the light source is a 300W xenon lamp containing a 420nm cutoff filter, and the light reaction time is 3 hours.
[0018] The beneficial effects of this invention include:
[0019] 1) In the constructed composite photocatalyst CaIn2S4 / T-COF, amorphous plate-like CaIn2S4 is grown in situ on the surface of spherical T-COF, which can provide more reactive sites and shorten the transport path of photogenerated electrons, thereby significantly improving photocatalytic activity;
[0020] 2) The synthesis process of this invention is simple, easy to operate, and produces products with high stability and yield, while also possessing excellent photocatalytic H2O2 production rate and HMF catalytic oxidation selectivity;
[0021] 3) The CaIn2S4 / T-COF composite photocatalyst for photocatalytic hydrogen peroxide production coupled with HMF oxidation prepared in this invention, in an air atmosphere, selects HMF instead of the traditional hole sacrificial agent. This can improve the performance of photocatalytic H2O2 production while selectively oxidizing HMF into the value-added chemical DFF using photogenerated holes, thus achieving the co-production of H2O2 and the high-value-added chemical DFF. This maximizes the solar energy utilization efficiency of the reaction system and saves production costs, showing high economic benefits and industrial application potential. This invention provides a new technical route for the development and application of bifunctional photocatalytic systems and opens up a new path for the synergistic development of clean production and green chemistry. Attached Figure Description
[0022] Figure 1 The images shown are scanning electron microscope (SEM) images and transmission electron microscope (TEM) images from Example 1.
[0023] Figure 2 The X-ray powder diffraction patterns of CaIn2S4, T-COF, and the complex CaIn2S4 / T-COF in Example 1 are shown below.
[0024] Figure 3 Thermogravimetric analysis (TGA) of CaIn2S4, T-COF, and the optimally proportioned complex CT-50 in Example 1 under nitrogen atmosphere;
[0025] Figure 4 This is a graph showing the rate of H2O2 production by photocatalysis of CaIn2S4, T-COF, and the complex CaIn2S4 / T-COF in Example 1.
[0026] Figure 5 The graph shows the rate of H2O2 production by the complex CT-50 in Example 1 under different conditions.
[0027] Figure 6 The graph shows the performance of photocatalytic oxidation of HMF to DFF by CaIn2S4, T-COF and the complex CaIn2S4 / T-COF in Example 1.
[0028] Figure 7 This is a graph showing the cyclic stability test of the complex CT-50 in Example 1.
[0029] Note: In Figure 1 In the image, (a) is a scanning electron microscope image of T-COF, (b) is a scanning electron microscope image of CaIn2S4, (c) is a scanning electron microscope image of the complex CaIn2S4 / T-COF, and (d) is a transmission electron microscope image of the complex CaIn2S4 / T-COF. Detailed Implementation
[0030] The technical solution of the present invention will now be described in detail with reference to the accompanying drawings and embodiments. It should be understood that the following embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Any modifications or substitutions made to the steps or conditions of the present invention without departing from the spirit and substance thereof are within the scope of the present invention.
[0031] Unless otherwise specified, the technical means used in the embodiments are conventional means well known to those skilled in the art.
[0032] Example 1: Preparation of the spherical core-shell composite photocatalyst CaIn2S4 / T-COF of the present invention
[0033] 1) Dissolve 126 mg (0.9 mmol) thiophene-2,5-dicarboxaldehyde and 211 mg (0.6 mmol) 1,3,5-tris(4-aminophenyl)benzene in 80 mL of acetonitrile, then add 9 mL of 12M acetic acid solution. Stir the resulting mixture at room temperature for 30 min. After standing for 3 days, centrifuge the reaction solution. Wash the resulting solid three times each with N,N-dimethylformamide, tetrahydrofuran, and ethanol. Finally, dry the washed product at 60 °C for 24 h to obtain the spherical covalent organic framework material T-COF with a yield of 89%.
[0034] 2) 20 mg of T-COF was ultrasonically dispersed in 30 mL of pure water, followed by the addition of 5.58 mg (0.05 mmol) CaCl2, 29.24 mg (0.10 mmol) InCl3·4H2O, and 15.03 mg (0.20 mmol) thioacetamide. After stirring at room temperature for 60 min, the mixture was transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner and heated to 120 °C for 24 h. After the reaction, the reaction solution was centrifuged, and the resulting solid was washed three times each with water and ethanol. Finally, the product was dried at 60 °C for 24 h to obtain the composite photocatalyst CaIn2S4 / T-COF (denoted as CT-50, which represents a sample with T-COF accounting for 50% of the theoretical total mass of the composite CaIn2S4 / T-COF), with a yield of 92%. Other composite samples CT-30 and CT-70 were synthesized according to the above method. If T-COF is not added during the above preparation process, a pure CaIn2S4 sample will be obtained.
[0035] Example 2: Preparation of the spherical core-shell composite photocatalyst CaIn2S4 / T-COF of the present invention
[0036] 1) 168 mg (1.2 mmol) of thiophene-2,5-dicarboxaldehyde and 211 mg (0.6 mmol) of 1,3,5-tris(4-aminophenyl)benzene were dissolved in 100 mL of acetonitrile, and then 9 mL of 6M acetic acid solution was added. The resulting mixture was stirred at room temperature for 1 min. After standing for 4 days, the reaction solution was centrifuged, and the resulting solid was washed three times each with N,N-dimethylformamide, tetrahydrofuran, and ethanol. Finally, the washed product was dried at 60 °C for 24 h to obtain the spherical covalent organic framework material T-COF with a yield of 85%.
[0037] 2) 20 mg T-COF was ultrasonically dispersed in 30 mL of pure water, followed by the addition of 5.58 mg (0.05 mmol) CaCl2, 29.24 mg (0.10 mmol) InCl3·4H2O, and 15.03 mg (0.20 mmol) thioacetamide. After stirring at room temperature for 60 min, the mixture was transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner and heated to 100 °C for 36 h. After the reaction, the reaction solution was centrifuged, and the resulting solid was washed three times each with water and ethanol. Finally, the product was dried at 60 °C for 48 h to obtain the composite photocatalyst CaIn2S4 / T-COF, with a yield of 90%.
[0038] Example 3: Preparation of the spherical core-shell composite photocatalyst CaIn2S4 / T-COF of the present invention
[0039] 1) 126 mg (0.9 mmol) of thiophene-2,5-dicarboxaldehyde and 316 mg (0.9 mmol) of 1,3,5-tris(4-aminophenyl)benzene were dissolved in 10 mL of acetonitrile, and then 9 mL of 12 M acetic acid solution was added. The resulting mixture was stirred at room temperature for 30 min. After standing for 2 days, the reaction solution was centrifuged, and the resulting solid was washed once each with N,N-dimethylformamide, tetrahydrofuran, and ethanol. Finally, the washed product was dried at 100 °C for 48 h to obtain the spherical covalent organic framework material T-COF with a yield of 82%.
[0040] 2) 20 mg of T-COF was ultrasonically dispersed in 70 mL of pure water, followed by the addition of 5.58 mg (0.05 mmol) CaCl2, 29.24 mg (0.10 mmol) InCl3·4H2O, and 30.06 mg (0.40 mmol) thioacetamide. After stirring at room temperature for 10 min, the mixture was transferred to a stainless steel high-pressure reactor with a polytetrafluoroethylene liner and heated to 180 °C for 12 h. After the reaction, the reaction solution was centrifuged, and the resulting solid was washed once with water and once with ethanol. Finally, the product was dried at 100 °C for 24 h to obtain the composite photocatalyst CaIn2S4 / T-COF, with a yield of 88%.
[0041] Example 4: Preparation of the spherical core-shell composite photocatalyst CaIn2S4 / T-COF of the present invention
[0042] The operation steps are the same as in Example 1, except that in step 1), the volume of acetonitrile is 10 mL, the molar ratio of thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene is 1:1, the concentration of acetic acid solution is 9 M, the static reaction is carried out at room temperature for 4 days, the solid obtained by centrifugation is washed once each with N,N-dimethylformamide, tetrahydrofuran and ethanol, the drying temperature is 80 °C and the drying time is 48 h, and the yield of the spherical covalent organic framework material T-COF is 85%; in step 2), the molar ratio of CaCl2, InCl3·4H2O and thioacetamide is 1:2:5, the volume of pure water is 40 mL, the stirring time at room temperature is 10 min, the hydrothermal reactor is heated to 100 °C and reacted for 36 h, the product is washed once each with water and ethanol, the drying temperature is 80 °C and the drying time is 48 h, and the yield of the composite photocatalyst CaIn2S4 / T-COF is 90%.
[0043] Example 5: Preparation of the spherical core-shell composite photocatalyst CaIn2S4 / T-COF of the present invention
[0044] The operation steps are the same as in Example 1, except that in step 1), the volume of acetonitrile is changed to 50 mL, the molar ratio of thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene is changed to 2:1, the static reaction is carried out at room temperature for 4 days, the solid obtained by centrifugation is washed twice each with N,N-dimethylformamide, tetrahydrofuran and ethanol, the drying temperature is 100 °C and the drying time is 36 h, and the yield of the spherical covalent organic framework material T-COF is 93%; in step 2), the molar ratio of CaCl2, InCl3·4H2O and thioacetamide is 1:2:6, the volume of pure water is 60 mL, the stirring time at room temperature is 20 min, the hydrothermal reactor is heated to 140 °C and reacted for 36 h, the product is washed twice each with water and ethanol, the drying temperature is 100 °C and the drying time is 36 h, and the yield of the composite photocatalyst CaIn2S4 / T-COF is 92%.
[0045] Example 6 Preparation of the spherical core-shell composite photocatalyst CaIn2S4 / T-COF of the present invention
[0046] The operation steps are the same as in Example 1, except that in step 1), the volume of acetonitrile is changed to 100 mL, the static reaction is carried out at room temperature for 4 days, the solid obtained by centrifugation is washed twice each with N,N-dimethylformamide, tetrahydrofuran and ethanol, the drying temperature is 100 °C and the drying time is 48 h, and the yield of the spherical covalent organic framework material T-COF is 91%; in step 2), the molar ratio of CaCl2, InCl3·4H2O and thioacetamide is 1:2:7, the volume of pure water is 70 mL, the hydrothermal reactor is heated to 160 °C and reacted for 36 h, the product drying temperature is 100 °C and the drying time is 36 h, and the yield of the composite photocatalyst CaIn2S4 / T-COF is 94%.
[0047] Example 7 Preparation of the spherical core-shell composite photocatalyst CaIn2S4 / T-COF of the present invention
[0048] The operation steps are the same as in Example 1, except that the concentration of acetic acid solution in step 1) is changed to 9M, the static reaction is carried out at room temperature for 2 days, the solid obtained by centrifugation is washed once each with N,N-dimethylformamide, tetrahydrofuran and ethanol, the drying temperature is 80 °C and the drying time is 48 h, and the yield of the spherical covalent organic framework material T-COF is 86%; in step 2), the molar ratio of CaCl2, InCl3·4H2O and thioacetamide is 1:2:8, the volume of pure water is 60 mL, the hydrothermal reactor is heated to 180 °C and reacted for 12 h, the product drying temperature is 80 °C and the drying time is 48 h, and the yield of the composite photocatalyst CaIn2S4 / T-COF is 92%.
[0049] Example 8: Application and performance testing of the composite photocatalyst CaIn2S4 / T-COF for photocatalytic H2O2 production coupled with HMF oxidation.
[0050] 10 mg of the composite photocatalyst CT-50 from Example 1 was added to 50 mL of pure water, followed by 5 mg of HMF. After ultrasonic dispersion, the temperature of the reaction system was controlled at 20 °C using a cooling water circulation pump. The mixture was stirred in the dark for half an hour in an air atmosphere. Then, a 300 W xenon lamp with a 420 nm cutoff filter was used as the light source, and the sample was collected after continuous illumination for 3 hours. The concentration of generated H2O2 was determined by iodometric titration, and the products of HMF photocatalytic oxidation were determined by high-performance liquid chromatography. The measured H2O2 production rate of the composite photocatalyst CT-50 was 2.14 mol g. -1 h -1 The HMF photocatalytic conversion rate was 93.04%, the HMF photocatalytic oxidation of DFF yield was 90.55%, and the DFF photocatalytic selectivity was 91.29%.
[0051] Example 9: Application and performance testing of the composite photocatalyst CaIn2S4 / T-COF for photocatalytic H2O2 production coupled with HMF oxidation.
[0052] 20 mg of the composite photocatalyst CT-50 from Example 1 was added to 50 mL of pure water, followed by 5 mg of HMF. After ultrasonic dispersion, the temperature of the reaction system was controlled at 20 °C using a cooling water circulation pump. The mixture was stirred in the dark for half an hour in an air atmosphere. Then, a 300 W xenon lamp with a 420 nm cutoff filter was used as the light source, and the sample was collected after continuous illumination for 1 hour. The concentration of generated H2O2 was determined by iodometric titration, and the products of HMF photocatalytic oxidation were determined by high-performance liquid chromatography. The measured H2O2 production rate of the composite photocatalyst CT-50 was 2.06 mol g. -1 h -1 The HMF photocatalytic conversion rate was 90.26%, the HMF photocatalytic oxidation of DFF yield was 88.36%, and the DFF photocatalytic selectivity was 82.58%.
[0053] Example 10: Application and performance testing of the composite photocatalyst CaIn2S4 / T-COF for photocatalytic H2O2 production coupled with HMF oxidation.
[0054] 5 mg of the composite photocatalyst CT-50 from Example 1 was added to 50 mL of pure water, followed by 5 mg of HMF. After ultrasonic dispersion, the temperature of the reaction system was controlled at 20 °C using a cooling water circulation pump. The mixture was stirred in the dark for half an hour in an air atmosphere. Then, a 300 W xenon lamp with a 420 nm cutoff filter was used as the light source, and the sample was collected after continuous illumination for 6 hours. The concentration of generated H2O2 was determined by iodometric titration, and the products of HMF photocatalytic oxidation were determined by high-performance liquid chromatography. The measured H2O2 production rate of the composite photocatalyst CT-50 was 1.94 mol g. -1 h -1 The HMF photocatalytic conversion rate was 86.36%, the HMF photocatalytic oxidation DFF yield was 82.66%, and the DFF photocatalytic selectivity was 81.73%.
[0055] Example 11 Photocatalytic production of H2O2 coupled with HMF oxidation by catalyst CaIn2S4 and performance testing
[0056] The operating procedure was the same as in Example 8, except that the catalyst was changed to CaIn2S4 at a dosage of 5 mg, and the irradiation time was 1 h. The measured photocatalytic H2O2 production rate of CaIn2S4 was 0.81 mol g. -1 h -1The HMF photocatalytic conversion rate was 45.95%, the HMF photocatalytic oxidation of DFF yield was 28.22%, and the DFF photocatalytic selectivity was 50.11%.
[0057] Example 12: Photocatalytic production of H2O2 by T-COF catalyst coupled with HMF oxidation and performance testing
[0058] The operating procedures were the same as in Example 8, except that the catalyst used in Example 8 was T-COF, the dosage was 20 mg, and the irradiation time was 6 h. The measured photocatalytic H2O2 production rate of T-COF was 0.92 mol g. -1 h -1 The HMF photocatalytic conversion rate was 39.41%, the HMF photocatalytic oxidation of DFF yield was 18.05%, and the DFF photocatalytic selectivity was 31.04%.
[0059] Materials Characterization and Performance Testing
[0060] Figure 1 The morphology of the synthesized materials was analyzed using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). T-COF exhibited a smooth, solid spherical morphology with a diameter of approximately 1 μm (Fig. 1a and 1d), while CaIn2S4 had an amorphous, plate-like structure (Fig. 1b and 1e). When CaIn2S4 was combined with T-COF, the composite material CaIn2S4 / T-COF still exhibited the spherical structure of T-COF, but its surface became rougher due to the covering of plate-like CaIn2S4 (Fig. 1c and 1f).
[0061] Figure 2 The X-ray powder diffraction pattern of the prepared sample is shown. The two characteristic diffraction peaks of T-COF at 2.46° and 25.34° can be attributed to the (100) and (001) crystal planes, respectively, indicating that it has good crystallinity.
[0062] CaIn2S4 (JCPDS card number 31-0272) exhibits sharp diffraction peaks at 28.5°, 33.1°, 43.5°, and 47.6°, corresponding to its (222), (400), (511), and (440) crystal planes, respectively. When CaIn2S4 is grown in situ on the surface of T-COF, these composite materials all exhibit the main diffraction peaks of CaIn2S4 and T-COF. As the content of T-COF in the composite gradually increases, it can be seen that the diffraction peak intensity of CaIn2S4 gradually decreases, while the diffraction peak intensity of T-COF gradually increases. However, no other impurity peaks were detected, indicating that the composite CaIn2S4 / T-COF was successfully prepared by the hydrothermal method.
[0063] Figure 3Thermogravimetric analysis (TGA) results of CaIn2S4, T-COF, and the optimally saturated complex CT-50 in a nitrogen atmosphere are shown. Figure 3 It can be seen that no significant weight loss was observed in any of the samples below 400 °C, indicating that they have excellent thermal stability.
[0064] Figure 4 These are the results of photocatalytic H2O2 production performance tests of CaIn2S4, T-COF, and the CaIn2S4 / T-COF composites (CT-30, CT-50, and CT-70) in an air atmosphere, using HMF instead of traditional sacrificial agents. The composite sample CT-50 showed the best performance, with a photocatalytic H2O2 production rate as high as 2.14 mol g. -1 h -1 The concentrations were 2.64 and 2.33 times that of pure CaIn2S4 and T-COF, respectively, indicating that the photocatalyst has potential practical value.
[0065] Figure 5 The results show the photocatalytic H2O2 production rate of the CT-50 composite under different conditions. Figure 5 It was found that both the electron scavenger AgNO3 and the superoxide radical scavenger p-benzoquinone significantly inhibited the formation of H2O2, indicating that electrons and superoxide radicals are key active species in the photocatalytic production of H2O2. The photocatalytic H2O2 production rate was significantly reduced without the addition of HMF, proving that HMF can act as a hole sacrificial agent to improve catalytic performance. Compared to an air environment, the photocatalytic H2O2 production rate was significantly increased in a pure oxygen atmosphere, while it plummeted in a nitrogen atmosphere, confirming that O2 is also an indispensable reactant in the photocatalytic H2O2 production process.
[0066] Figure 6 The results show the photocatalytic selective oxidation performance of HMF by CaIn2S4, T-COF, and the complexes CaIn2S4 / T-COF (CT-30, CT-50, and CT-70) in air atmosphere. Figure 6 As shown, the HMF conversion, DFF selectivity, and DFF yield of T-COF and CaIn2S4 all fell below 50%. The composite sample CT-50 showed the best performance in photocatalytic oxidation of HMF into DFF, with HMF conversion, DFF yield, and DFF catalytic selectivity all exceeding 90%.
[0067] Figure 7 These are the results of the cyclic stability test of the CT-50 complex. Figure 7 It can be seen that after four consecutive cycles of reaction, the CT-50 complex still maintains more than 90% of its initial photocatalytic H2O2 production and photocatalytic oxidation of HMF to DFF performance, which confirms that it has excellent photocatalytic performance stability.
[0068] The above description is only a preferred embodiment of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any changes, equivalent substitutions, permutations and combinations made without departing from the essence and principle of the present invention should be considered equivalent substitutions and should be included within the protection scope of the present invention.
Claims
1. A composite photocatalyst CaIn2S4 / T-COF, which is a spherical core-shell structure formed by amorphous sheet-like CaIn2S4 covering the surface of T-COF.
2. A method for preparing the composite photocatalyst CaIn2S4 / T-COF as described in claim 1, characterized in that... Includes the following steps: 1) Using thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene as raw materials and acetonitrile as solvent, Synthesizing spherical covalent organic framework material T-COF at room temperature; 2) The composite photocatalyst CaIn2S4 / T-COF is obtained by combining the sheet-like CaIn2S4 with the T-COF through a hydrothermal reaction.
3. The preparation method of the composite photocatalyst CaIn2S4 / T-COF as described in claim 2, characterized in that: Step 1) involves adding thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene to acetonitrile, followed by... Add the mixture to an acetic acid solution, sonicate and stir, and allow it to stand to react. Centrifuge the reaction solution, wash the resulting solid, and dry it to obtain T-COF. Step 2) involves ultrasonically dispersing the T-COF obtained in step 1) in pure water, and adding CaCl2 and InCl3. 4H2O and thioacetamide were stirred, and the reaction solution was poured into a reaction vessel and heated to react. After centrifugation, washing and drying, the composite photocatalyst CaIn2S4 / T-COF was obtained.
4. The preparation method of the composite photocatalyst CaIn2S4 / T-COF as described in claim 3, characterized in that: In step 1), the molar ratio of thiophene-2,5-dicarboxaldehyde and 1,3,5-tris(4-aminophenyl)benzene is 1:
1. The ratio is 2:1, the amount of acetonitrile used is 10-100 mL; the amount of acetic acid solution is 6-12 mol / L. -1 The stirring is performed at room temperature for 1–30 min; the static reaction is allowed to stand at room temperature for 2–4 days; the washing is performed by washing with N,N-dimethylformamide, tetrahydrofuran, and ethanol 1–3 times each; the drying temperature is 60–100 °C, and the drying time is 24–48 hours. In step 2), the amount of pure water used is 30–70 mL; the molar ratio of CaCl2, InCl3·4H2O, and thioacetamide is 1:2:4–1:2:8; the stirring is carried out at room temperature for 10–60 min; the reaction vessel is a stainless steel high-pressure reaction vessel with a polytetrafluoroethylene liner; the heating reaction is carried out by heating the reaction vessel to 100–180℃ for 12–36 h; the washing is carried out by washing with water and ethanol 1–3 times each; the drying temperature is 60–100℃ and the drying time is 24–48 hours.
5. The application of the composite photocatalyst CaIn2S4 / T-COF as described in any one of claims 1 to 4, wherein the application is to achieve highly selective catalytic oxidation of HMF to DFF while simultaneously producing H2O2 through photocatalysis.
6. The application as described in claim 5, wherein the application method is as follows: A certain amount of the composite photocatalyst CaIn2S4 / T-COF and HMF were dissolved in pure water, and the temperature was controlled at 20 °C. The mixture was stirred in the dark for half an hour in an air atmosphere, and then the reaction was continuously irradiated for a certain period of time to obtain H2O2 and DFF. The ratio of HMF to pure water was 1 mg: 5 mL.
7. The application as described in claim 6, characterized in that: The amount of the composite photocatalyst CaIn2S4 / T-COF is 1 to 4 times the mass of the HMF, the temperature is controlled by a cooling water circulation pump, and the photo-reaction time is 1 to 6 hours.
8. The application as described in claim 7, characterized in that: The light source is a 300 W xenon lamp containing a 420 nm cutoff filter, and the light reaction time is 3 hours.